CIRCUIT ANALOG OF ELECTRON TEMPERATURE FLUCTUATIONS AS A METHOD OF NUMERICAL SIMULATION OF THE HELICAL SHAPE OF AN ELECTRIC ARC PLASMA IN AN EXTERNAL AXIAL MAGNETIC FIELD (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
A description of a circuit analog of electron temperature fluctuations as a method of numerical simulation of the helical spatial shape of an electric arc in an external axial magnetic field is presented. The circuit analog of fluctuations generates randomly an asymmetry of the electron temperature distribution and, as a consequence, other characteristics of the arc plasma. The resulting asymmetry in the distribution of arc characteristics is “picked up” by an external axial magnetic field and can contribute to the formation of the helical structure of the arc column.
Keywords: DC electric arc; external axial magnetic field; helical shape of the arc column